2012
DOI: 10.1167/iovs.11-7631
|View full text |Cite
|
Sign up to set email alerts
|

Latency Measures of Pattern-Reversal VEP in Adults and Infants: Different Information from Transient P1 Response and Steady-State Phase

Abstract: In this study, the effectiveness of the phase-based method to calculate latency was confirmed. In infants, the rapid decrease of P1 latency may be due to the progressive maturation of conduction time in the afferent visual pathways, with the development of adult levels of phase-based calculated latency being due to the maturation of later cortical processing in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
25
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 47 publications
7
25
2
Order By: Relevance
“…The adult brain has a highly interconnected, sophisticated architecture that readily exhibits changes based on expectations (2,3,33). Young infants presumably lack both the sophisticated internal models of the environment and the well-honed sensorimotor processing abilities of adults and are slower to process even basic stimuli (13). In addition, connections in the infant brain are not mature and experience a robust developmental trajectory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adult brain has a highly interconnected, sophisticated architecture that readily exhibits changes based on expectations (2,3,33). Young infants presumably lack both the sophisticated internal models of the environment and the well-honed sensorimotor processing abilities of adults and are slower to process even basic stimuli (13). In addition, connections in the infant brain are not mature and experience a robust developmental trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, converging evidence from both anatomical (10) and functional connectivity analyses (11) has demonstrated that human infants have a much less interconnected brain and instead have a predominance of local connections and a slow development of long-range interactions (12). Finally, human infants exhibit characteristically slower neural processing even for basic sensory stimuli (13).…”
mentioning
confidence: 99%
“…Such delayed maturation for global visual processing is thought to be a consequence of restricted interactions between spatial cues at an earlier age (Kovács et al, 1999) as well as underdeveloped long-range connections (Gervan, Berencsi, & Kovács, 2011). Likewise, feedback and horizontal connections, which are useful for integrating contours, demonstrate delayed maturation (Lee, Birtles, Wattam-Bell, Atkinson, & Braddick, 2012). Along with delayed maturation, feedback pathways are also less synchronized at an early age, which might result from diminished myelination, maturation, and learning through repeated exposure (Werkle-Bergner, Shing, Müller, Li, & Lindenberger, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There is a general agreement that a decrease in transient P1 peak latency or an analogous shift in ssVEP phase can be explained by shorter response time and/or faster retino-cortical processing of the visual information. 23,50,51 Decreased retinal illumination is one of the factors that increases P1 peak latency 39,52,53 and also introduces a clockwise shift in RP-VEP 51 and DRDC-VEP phases, 39 which will consequently elongate response time to the visual stimulus and slow down visual information processing in the visual system. In the present study, we found an opposite (i.e., counterclockwise) phase shift in DRDC-VEP phase and a decrease in P1 peak latency as a function of age, which suggests gradually shorter response time and faster retino-cortical and may be intracortical visual information processing in the brain during development.…”
Section: Development In Preterm Versus Full-term Infantsmentioning
confidence: 99%
“…12,13,[18][19][20][21] In full-term infants, there is a rapid decrease in P1 peak latency from approximately 260-300 ms to the adult-like 100 ms in the first 15 postnatal weeks for large (120 minutes of arc) check sizes. 10,16,22,23 Numerous VEP experiments have demonstrated that maturation of P1 peak latency is not affected by visual experience (i.e., additional visual experience in preterm infants does not accelerate the maturation of P1 peak latency). 10,24 Experience-independence suggests that this development is driven by intrinsic molecular and neuronal processes and most likely is associated with retinal development, synaptogenesis, development of synapses, and myelination of the nerve fibers in the visual pathways and elsewhere in the brain.…”
mentioning
confidence: 99%